2016
DOI: 10.4236/ojpm.2015.66015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Specific Healthy Behaviors Positively Associated with General Life Satisfaction among Rural Adults

Abstract: Background: Chronic diseases are the leading causes of death worldwide. Evidence suggests that infrequent adopting healthy behaviors correlated with many chronic diseases. Healthy behaviors can lead to a marked reduction of morbidity and mortality. Life satisfaction is an important parameter of well-being. Few studies have focused on the association between healthy behaviors and life satisfaction among adults in rural areas. Aim: To establish the determinant and modifiable lifestyle factors associated with lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The results showed high prevalence of tooth loss and <20 remaining teeth in adults in rural areas. These findings are consistent with those of previous researches examining the prevalence of and factors associated with tooth loss in rural communities, which characterized with low educational levels, infrequent use of dental floss, and high prevalence of smoking [ 4 , 24 , 25 ]. The results also echoed the statements by WHO [ 1 ] that social determinants in oral health are very strong.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed high prevalence of tooth loss and <20 remaining teeth in adults in rural areas. These findings are consistent with those of previous researches examining the prevalence of and factors associated with tooth loss in rural communities, which characterized with low educational levels, infrequent use of dental floss, and high prevalence of smoking [ 4 , 24 , 25 ]. The results also echoed the statements by WHO [ 1 ] that social determinants in oral health are very strong.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have shown that individuals, who smoked and did not attend regular dental check-ups, nor brush their teeth, adhere to a balanced diet, nor consume vegetables or water, would frequently reported lower levels of satisfaction with life [ 1 , 24 ]. In addition, “8020 achievers” exhibited higher daily activity levels, greater satisfaction with life, and higher cumulative survival rates relative to those of “8020 non-achievers” [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate at least several reasons that might account for the disparities reported by our Taichung sample: First, medical resources were insufficient for the current Taiwanese older adults during their childhood and youth compared with the younger cohorts in Taiwan. Second, due to insufficient oral health literacy (Ho et al, 2019; Hsu et al, 2013), most of the older adults in Taiwan often reported poor oral hygiene perceptions and behaviors (Hsu et al, 2013; Lin et al, 2016; Wang et al, 2013). As a result, they tended to suffer from serious oral health problems and had poor self-rated oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Some literature supports that healthy eating and exercise are associated with health status, e.g. decreasing the chances of being overweight and developing cardiovascular diseases, and increasing general life satisfaction [5,23]. Therefore, even outside of the context of suicide prevention, a healthy lifestyle for people with disabilities is an important health focus for community health nurses.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Health-related behaviours were modified from the health promotion scale [19][20][21][22] and evidenced by the presence of specific healthy behaviours positively associated with general life satisfaction and health status [23,24]. This modified questionnaire contained 6 domains; including substance use, exercise, and nutrition, sleeps quality, social participation, and life satisfaction in the past year.…”
Section: Instruments (1)mentioning
confidence: 99%